Los retos de la formación por competencias del contador público - Dextre Flores, José Carlos (2013)
The interest of this paper is based on presenting the importance of educational instruction today, in general and in particular the accounting career. This, it should be noted, is part of the development trends of cognitive skills, instrumental skills and values that a person must acquire during the education period at a higher educational institution, which will allow the graduate to be competent to begin the professional practice.The complexity that is involved in the public accountant career in both their education based on international standards like the attributes to be displayed in the quality of performance, has forced higher education experts to guide newways of undertaking the education strategy. This is accomplished through the adoption of models consistent with the demands of society and the employment market. Of these, competencies education is one of the models that best contribute to the learning process, allowing at the potential accounting professional to develop skills, abilities and attitudes needed to join into the labor market successfully. In this sense, the college, university, or an academic unit faculty, school, program) - they decided to adopt, provide and ensure competencies education, mustdo according to the guidelines proposed for teaching methodologies, social responsibility and the business world. Similarly, should be based on participatory action committed by students and teachers, and the respect for human values. Within this scheme, it must prioritize the humanistic education of the person in their professional projection.